Avaliação bioquímica e hostológica de fígado de ratas wistar diabéticas e tratadas com tamoxifeno - Jatobá, Carlos André Nunes (2007)
Tamoxifen (TX), a drug used in the treatment of breast cancer, may cause hepatic changes in some patients. The consequences of its use on the liver tissues of rats with or without diabetes mellitus (DM) have not been fully explored. The purpose of this multidisciplinary study was to evaluate the correlation between plasma hepatic enzyme levels and the presence of iron overload in the hepatic tissue of female Wistar rats with or without streptozotocin-induced DM and using TX. Female rats were studied in control groups: C-0 (non-drug users), C-V (sorbitol vehicle only) and C-TX (using TX). DM (diabetic non-drug users) and DM-TX (diabetics using TX) were the test groups. Sixty days after induced DM, blood samples were collected for glucose, alanine aminotransferase (ALT), aspartate aminotransferase (AST) alkaline phosphatase (ALP) and bilirubin measures. Hepatic fragments were processed and stained with hematoxylin and eosin (H&E), Masson s trichrome, Perls. The hepatic iron content was quantified by atomic absorption spectrometry. AST, ALT and ALP levels were significantly elevated in the DM and DM-TX groups, with unchanged bilirubin levels. Liver iron overload using Perls stain and atomic absorption spectrometry were observed exclusively in groups C-TX and DM-TX. There was positive correlation between AST, ALT and ALP levels and microscopic hepatic siderosis intensity in group DM-TX. In conclusion, TX administration is associated with liver siderosis in diabetic and non-diabetic rats. In addition, TX induced liver iron overload with unaltered hepatic function in 2 non-diabetic rats and may be a useful tool for investigating the biological control of iron metabolism